ANALISIS PENCAPAIAN KETERAMPILAN KOMUNIKASI PADA PROSES PEMBELAJARAN - Astri Junita Putri; Arsil Arsil (JRPD (Jurnal Riset Pendidikan Dasar), 2020)
This study aims to describe the achievement of communication skills in the learning process and the factors that influence students in VA VA 64 Muara Bulian. The approach in this study uses a qualitative approach to the type of ednographic research. Data collection techniques through observation, interviews and documentation. This research data in the form of a description of the results of observations about communication skills and explanation of the results of interviews about communication skills with the homeroom teacher. Data analysis techniques in this study used Miles and Hubberman analysis. The results of this study indicate that students are able to complete the tasks given by the teacher well, although there are some students who finish them while playing. In verbal ideas are good, although there are still students who are shy. The use of communication in a variety of objectives has begun to be implemented, this is evidenced by the presence of peer tutors. Learners have also been able to conduct experiments and make reports on the results of experiments and then convey the results of these experiments.